A model coupling current non-adjustable, coming adjustable and remaining stages for daily generation scheduling of a wind-solar-hydro complementary system. (15th January 2023) - Huang, Kangdi; Liu, Pan; Kim, Jong-Suk; Xu, Weifeng; Gong, Yu; Cheng, Qian; Zhou, Yong
Abstract: To formulate the daily generation scheduling of a wind-solar-hydro complementary system (WSHCS), the hourly forecasts of the reservoir inflow, wind speed, and sunlight intensity within a day and their longer prediction can be used to assess the benefit of the day-ahead and remaining stages, respectively. Thus, the current two-stage model coupling these forecasts can efficiently maximize the total benefits of day-ahead and remaining stages. However, the two-stage model does not consider the significant difference between non-adjustable and adjustable periods for hydropower. Namely, the hydro unit commitment should be decided in the current stage (non-adjustable period), and it can be adjusted in the coming stage (adjustable period). To address this issue, a three-stage model, including the day-ahead non-adjustable stage, the day-ahead adjustable stage, and the remaining period stage, is proposed to formulate a daily generation scheduling of the WSHCS. The Guandi wind-solar-hydro hybrid power plant on China's Yalong River is selected as a case study. Results show that compared with the two-stage model, the proposed three-stage operation model can increase the average energy production of the WSHCS by 2.23 GWh for typical days, and the average power curtailment rate reduces by 0.26%. A three-layer nested approach can simplify from 576 to 26 decision variables for the high-dimensional three-stage model, and improve the computational efficiency. Thus, the proposed method could guide the daily generation scheduling of a WSHCS. Highlights: A model coupling current non-adjustable, coming adjustable and remaining stages is proposed. A benefit-risk indicators system considering three-stage is established. A three-layer nested approach is used to solve the high-dimension model. The proposed model provides guidance for daily generation scheduling.